Sınıf Iıı Anomalilerde Sınıf Iıı Elastikler Ve Chın-Cap İle Yapılan Tedavinin Etkilerinin İncelenmesi (2 Olgu Nedeni İle) - Gülnaz Leblebicioğlu Marşan (Galenos Yayinevi, 1998)
The aim of the study was to investigate the relationships between the cant of posterior occlusal plane, anterior occlusal plane and occlusal plane, and craniofacial structures in class II division I malocclusions. Skeletal parameters were divided two groups according to their relations. Forty patients with class II division I malocclusion and twenty-three patients with class I occlusion were evaluated. In this study, the relations between skeletal parameters and posterior, anterior occlusal planes and occlusal plane were assessed by path analysis. The findings indicated that the cant of the occlusal plane and posterior occlusal plane were related to SNB, BaNaGn angles and, anterior occlusal plane was correlated with SNB, SNA, ANB angles in class II division 1 malocclusion. In class I occlusion, the three occlusal planes were significantly related to SNA angle. The percentage effect of mandibular parameters on the cant of the occlusal planes was higher in class II division I malocclusion, than the percentage effect in class I occlusion. In conclusion, mandibular retrusion affected occlusal plane and anterior and posterior occlusal planes.